Cytotoxicity Properties of Full Subsituted Organocyclophosphazene Derivatives Containing chalcone-groups against A2780 and MCF-7 Cancer Cell Lines - Durmus, Merve; Beytur, Asiye; Celik, Mesut; Disli, Faruk; Koran, Kenan; Tekin, Suat; Sandal, Suleyman (Wiley, 2017)
[Abstract Not Available]